Community Indifference - Baumol, William J. (Review of Economic Studies, 1946)
Journal Article Community Indifference Get access William J. Baumol William J. Baumol New York and London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 1, 1946, Pages 44–48, https://doi.org/10.2307/2295757 Published: 01 April 1946